DIGITAL DATA SECURITY IN BLOCKCHAIN NETWORKS - Abduvositov Khumoyun Fakhriddin ogli , Inoyatov Ogabek Ibodullayevich (Miasto Przyszłości, 2024)
This article explores the important problem of ensuring digital data security in blockchain networks. Blockchain, as a decentralized system for storing and transmitting information, has become an integral part of the modern digital world and has found wide application in various industries. However, despite their reliability and integrity, blockchain networks are also susceptible to data security threats.